2009
DOI: 10.1080/15389580802382671
|View full text |Cite
|
Sign up to set email alerts
|

Case Study: Report of Nine Cases of Posterior Hip Dislocations in a Single Accident Involving a Modified Minibus

Abstract: We recommend that the authorities put a stop to uncensored vehicle modifications to reduce hip injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Avascular necrosis of the femoral head is a known complication of traumatic hip dislocation and reduction within 12 h has been recommended by clinical studies as the golden time for reduction 31. In a more recent study by Hougaard and Thomsen,33 avascular necrosis of the femoral head was reported in 4.8% of hips reduced within 6 h and 52.9% in hips reduced after 6 h within a minimum follow-up of 5 years. However, Reigstad34 found a zero incidence of osteoarthritis or avascular necrosis in simple dislocations reduced within 6 h. Good results have been reported in patients with early, stable, and accurate reductions by either closed or open methods 1934.…”
Section: Discussionmentioning
confidence: 99%
“…Avascular necrosis of the femoral head is a known complication of traumatic hip dislocation and reduction within 12 h has been recommended by clinical studies as the golden time for reduction 31. In a more recent study by Hougaard and Thomsen,33 avascular necrosis of the femoral head was reported in 4.8% of hips reduced within 6 h and 52.9% in hips reduced after 6 h within a minimum follow-up of 5 years. However, Reigstad34 found a zero incidence of osteoarthritis or avascular necrosis in simple dislocations reduced within 6 h. Good results have been reported in patients with early, stable, and accurate reductions by either closed or open methods 1934.…”
Section: Discussionmentioning
confidence: 99%